2006
DOI: 10.1002/nag.543
|View full text |Cite
|
Sign up to set email alerts
|

Modelling mechanical behaviour of limestone under reservoir conditions

Abstract: High porosity and low permeability limestone has presented pore collapse. As fluid is withdrawn from these reservoirs, the effective stresses acting on the rock increase. If the strength of the rock is overcome, pore collapse may occur, leading to irreversible compaction of porous media with permeability and porosity reduction. It impacts on fluid withdrawal. Most of reservoirs have been discovered in weak formations, which are susceptible to this phenomenon. This work presents a study on the mechanical behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…They obtained an R-value of 4. Coelho et al [28] reported an R-value of 6.3 for Limestone with a porosity of 20-30%. Using a triaxial press they found an R-value of 6.3.…”
Section: Cap Eccentricity Parameter Rmentioning
confidence: 97%
“…They obtained an R-value of 4. Coelho et al [28] reported an R-value of 6.3 for Limestone with a porosity of 20-30%. Using a triaxial press they found an R-value of 6.3.…”
Section: Cap Eccentricity Parameter Rmentioning
confidence: 97%
“…3. Mowar et al (1996), Brazilian limestone data are from Coelho et al (2006), Indiana limestone data are the same as in Lomov et al (2005).…”
Section: Porous Compaction and Dilationmentioning
confidence: 98%
“…As shown in Fig (Walsh, 1965) using two different Poisson ratios, the markers are the experimental data (Baud et al, 2000a;Mowar et al, 1996;Vajdova et al, 2004;Coelho et al, 2006). …”
Section: Elastic Properties and Poroelasticitymentioning
confidence: 99%
“…The model captures effects of shear-enhanced compaction as it is shown in Fig.1.4 where uniaxial and hydrostatic compaction of sandstones of different porosity is compared with the model. Solnhofen limestone data are from [13], Cordoba Limestone data are from [14], Brazilian limestone data are from [15], Indiana limestone data are the same as in [16] The material model used in this study is thermodynamically consistent and applicable to shock wave loading regime. It was developed to be applied not only for small scale rock samples but also for isotropic rock masses under assumptions that the joints are randomly distributed and overall response remains isotropic.…”
Section: Summary Of the Current Approachmentioning
confidence: 99%
“…The bulking shift, µ b , is proportional to the amount of bulking porosity,φ 2 , as 15) whereγ controls the rate of compaction of porosity produced by bulking. The bulking porosity,φ 2 , is a history variable describing extra porosity produced by dilatancy using the following equation:…”
Section: Constitutive Modeling Frameworkmentioning
confidence: 99%